2002
DOI: 10.1038/oby.2002.125
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Slimming Behavior in Denmark in 1992 and 1998

Abstract: observational study of slimming behavior in Denmark in 1992. Obes Res. 200210:911-922. Objective: To elucidate how frequent weight-loss attempts are made, the methods used to achieve weight loss, and the extent to which the outcome is positive. Research Methods and Procedures: Two independent interviews were conducted in 1992 and in 1998, each with 1200 randomly selected adult subjects. Each survey was designed to ensure an equal distribution of age, gender, and geographical regions in Denmark. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 20 publications
(20 reference statements)
1
34
0
2
Order By: Relevance
“…In a Danish study interviews with 1200 men and women revealed that approximately half of this population had attempted to lose weight. 2 Also here the prevalence of trying to lose weight increased with BMI.…”
Section: Introductionmentioning
confidence: 76%
“…In a Danish study interviews with 1200 men and women revealed that approximately half of this population had attempted to lose weight. 2 Also here the prevalence of trying to lose weight increased with BMI.…”
Section: Introductionmentioning
confidence: 76%
“…Nevertheless, multiple studies have shown that men to a lesser extent than women try to lose weight, and significant fewer men than women participate in organized weight reduction programmes (French and Jeffery, 1994;Bendixen et al, 2002). Several reasons for this could be hypothesized: men are perhaps not motivated for weight loss, or they may perceive too many barriers towards weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…(Kjøller and Rasmussen, 2002). Overweight and obese men are more likely than women to carry excess body fat around their waist and upper abdomen, which is associated with an increased risk of many health problems and men may benefit more from weight loss than women, because of the change in fat distribution following weight loss (Wirth and Steinmetz, 1998).Nevertheless, multiple studies have shown that men to a lesser extent than women try to lose weight, and significant fewer men than women participate in organized weight reduction programmes (French and Jeffery, 1994;Bendixen et al, 2002). Several reasons for this could be hypothesized: men are perhaps not motivated for weight loss, or they may perceive too many barriers towards weight reduction.…”
mentioning
confidence: 99%
“…Because slimming prevalence increases with increasing body mass index (BMI), 3,11 it is often assumed that weight cycling is above all a problem of obese subjects. Indeed, a high prevalence of voluntary weight loss attempts has been reported in overweight and obese subjects in various studies.…”
Section: Introductionmentioning
confidence: 99%